HOW TO IMPROVE IELTS WRITING TASK 2 - Ergasheva Odinabonu Ikrom qizi,; Bozorova Sevinch Ravshan qizi,; Abduvoxitova Shaxnoza Baxrom qizi,; Usanova Mashhura Erkin qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article describes in detail why writing is a difficult part of language acquisition and what can be done to solve language problems related to this. It mostly focuses on IELTS writing task 2 and gives information about how to get a high score from writing portion of the test. Additionally, there are some sample essay in the end so that given explanation can be more comprehensible.